Zastaranje odškodninskega zahtevka zoper (nekdanjega) člana organa vodenja gospodarske družbe - Drobnič, Tamara (Podjetje in delo, 2020)
The paper examines the statute of limitations of a claim against a member of the management board, and attempts to answer when the limitation period in question begins to run. In doing so, it distinguishes between the limitation period before and after the adoption of the amendment to the Companies Act (ZGD-1I), when the limitation period was enacted under the umbrella regulation governing companies. In this paper, I first highlight the current situation in Slovenia by analysing publicly available Slovenian case law. With a simple case, where a member of the management body breaches their duties, I substantiate the start of the limitation period. In the last part, I also present a look at the statute of limitations of such claims from the point of view of German law, which has provided rich relevant case law throughout the years.
Keywords: claim for damages; commercial law; diligence and liability; gospodarsko pravo; knowledge of a legal entity; liability for damages; limitation period; management liability; odgovornost poslovodnih organov; odškodninska odgovornost; odškodninski zahtevek; skrbnost in odgovornost; time-barring; védenje pravne osebe; zastaralni rok; zastaranje